Intimacy That Hurts: A Portrait of Dating Violence Among Victims of Blackmail - Asyananda Pramesti, Stefani; Huwae, Arthur (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The phenomenon of blackmailing in dating relationships is a serious issue as it is often accompanied by dating violence that negatively affects victims’ mental health. Blackmailing in dating relationships also has a profound impact on victims’ overall lives. The aim of this study is to explore the portrait of dating violence among individuals who have experienced blackmailing. This study employed a qualitative approach with a descriptive phenomenological design. Participants consisted of three individuals aged 18–25 who had experienced blackmailing, selected through snowball sampling. Data were collected through in-depth interviews and unstructured observations, and the credibility of the study was ensured using data triangulation. The findings reveal that participants experienced various forms of dating violence, including social withdrawal and isolation, humiliation that lowered self-esteem, coercion to fulfill partners’ sexual demands, repeated threats that created fear, and emotional manipulation that made victims feel powerless. In addition, some participants experienced extortion for the perpetrators’ benefit. 7 These findings provide a deeper understanding of victims’ experiences, which may help them recognize the impact they have endured and encourage them to find positive ways to move forward. This study also highlights the importance of social support and assistance to ensure a more effective psychological recovery process for victims.Fenomena blackmailing dalam hubungan berpacaran merupakan masalah serius karena sering kali diikuti dengan dating violence yang berdampak pada kesehatan mental korban. Persoalan blackmailing dalam hubungan berpacaran juga memberikan dampak besar terhadap kehidupan korban secara menyeluruh. Tujuan penelitian ini adalah untuk mengetahui potret dating violence pada individu korban blackmailing. Penelitian menggunakan pendekatan kualitatif dengan desain fenomenologi deskriptif. Partisipan terdiri dari tiga individu berusia 18–25 tahun yang pernah mengalami blackmailing, dipilih melalui teknik snowball sampling. Data dikumpulkan melalui wawancara mendalam dan observasi tidak terstruktur, kemudian diuji kredibilitasnya dengan triangulasi data. Hasil penelitian menunjukkan bahwa partisipan mengalami berbagai bentuk dating violence, antara lain penarikan dari lingkungan sosial hingga merasa terisolasi, penghinaan yang menurunkan harga diri, pemaksaan dalam memenuhi kebutuhan seksual pasangan, ancaman berulang yang menimbulkan ketakutan, serta manipulasi emosional yang membuat korban merasa tidak berdaya. Selain itu, ditemukan pula bentuk pemerasan demi kepentingan pelaku. Temuan ini memberikan gambaran mendalam mengenai pengalaman korban, sehingga dapat membantu mereka memahami dampak yang dialami dan berupaya melihat sisi positif untuk melanjutkan kehidupan. Penelitian ini juga menegaskan pentingnya dukungan sosial dan pendampingan bagi korban agar proses pemulihan psikologis dapat berlangsung lebih efektif.